THE DISTRIBUTION OF SCIENCE ACCORDING TO MUSLIM PHILOSOPHERS - Hasan Bakti Nasution; M. Fajri Syahroni Siregar; Imron Bima Saputra (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
This research is qualitative research and includes literature research. The purpose of this study is to examine the distribution of knowledge with various branches and scopes. This research uses a descriptive method with a qualitative approach. The results of this study show that the concept of science in the Middle Ages and Muslim scientists including Al Farabi, Ibn Khaldun, Al Ghazali, and other scientists basically still has no classification of science on the one hand and religion on the other. The classification of knowledge given by experts at this time aims to make it easier for humans to study science so that humans have certain expertise in scientific disciplines, and do not deny other sciences so that there is a balance in themselves that brings benefits. The Islamic view of science is quite comprehensive. Science can be equated with science in the Western tradition, but Islam has a broader meaning. The scope of knowledge in Islam is not limited to the physical and observable, but also includes aspects of metaphysics.